Broadband reflection in polymer-stabilized cholesteric liquid crystals via spin-coating MoO2 nanoparticles. (29th November 2022) - Zhao, Yuzhen; Li, Chaonian; Lang, Tingting; Li, Jinqian; Guo, Zhun; Yao, Ruijuan; Gao, Jianjing; Zhao, Yang; Wang, Dong
Abstract : The SEM image of the polymer network of samples e1–e5: (e1) 4.8% C6M ; (e2) 6.8% C6M ; (e3) 8.8% C6M ; (e4) 10.8% C6M ; (e5) 12.8% C6M ; and (e4′) cross-sectional image of e4. Abstract : Cholesteric liquid crystals (ChLC) with helical molecular structures are known for their ability to selectively reflect light at specific wavelengths. In this study, broadband reflective polymer-stabilized cholesteric liquid crystal (PSCLC) films in the near-infrared region were prepared by spin-coating MoO2 nanoparticle (NP) dispersions. The effects of the dispersion concentration, the concentration of the polymerizable monomer, the light intensity and the polymerization time on the reflection wavelength were studied. The reflection bandwidth of the PSCLC film was broadened from 261 nm to 401 nm. It is confirmed that NPs have photothermal conversion ability, and their diffusion in the liquid crystal composite system is beneficial to the formation of non-uniform pitch distribution. Therefore, the PSCLC film prepared by the NP diffusion method is expected to be used for dynamic control of the sunlight transmission of energy-saving glass in buildings.